9z+2-4=4+4z-6

Simple and best practice solution for 9z+2-4=4+4z-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9z+2-4=4+4z-6 equation:


Simplifying
9z + 2 + -4 = 4 + 4z + -6

Reorder the terms:
2 + -4 + 9z = 4 + 4z + -6

Combine like terms: 2 + -4 = -2
-2 + 9z = 4 + 4z + -6

Reorder the terms:
-2 + 9z = 4 + -6 + 4z

Combine like terms: 4 + -6 = -2
-2 + 9z = -2 + 4z

Add '2' to each side of the equation.
-2 + 2 + 9z = -2 + 2 + 4z

Combine like terms: -2 + 2 = 0
0 + 9z = -2 + 2 + 4z
9z = -2 + 2 + 4z

Combine like terms: -2 + 2 = 0
9z = 0 + 4z
9z = 4z

Solving
9z = 4z

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '-4z' to each side of the equation.
9z + -4z = 4z + -4z

Combine like terms: 9z + -4z = 5z
5z = 4z + -4z

Combine like terms: 4z + -4z = 0
5z = 0

Divide each side by '5'.
z = 0

Simplifying
z = 0

See similar equations:

| 5(x+3)=10-2(x+2) | | 2(120-5x/10) | | -30-6n=-10-2(3n+10) | | 1.2=0.1x | | 3x+2(x-2)+9=0 | | x-(.3x)=28 | | (.3x)-x=28 | | 10-k=k-6 | | 0.41x+x=117 | | 3*(x+1)=2*(x+11) | | x^2-13x-23=-4x-1 | | .3x-x=28 | | -3(-5v-4v-4y+3)= | | (4x^(2/7))(3x^(1/3)) | | 9*(z-3)=12z | | 5x-105=-4x+30 | | -3x-7+2x+5x-11x= | | 5x-x-7=-4x+2 | | (3x+1)+4i=-2+(3y-2)i | | 0.5x^2-3x+4=0 | | 10x+64+5x=65x-36 | | -3-2(6)= | | -2(x+6)+3x= | | 3x-10=5x+45 | | 6y=10x-4 | | 3x+2y=73 | | 5x-6+6x-8=x+4+x+10 | | x^2+8=-8x+1 | | 10x-7y=11 | | 600t^2+60t-3=0 | | 140=x^(1/2) | | 140=x^1/2 |

Equations solver categories